Relationships Between the Rulers of the Archipelago (Perspective of Traditional Javanese Historiography) - Sudirman Shomary; Roziah Roziah; Muhammad Mukhlis; Nurul Aini Sudirman (Universitas Cokroaminoto Palopo, 2026)
This study examines the representation of relationships among Nusantara rulers through the lens of traditional Javanese historiography, including Nagarakertagama, Pararaton, and various Babad texts. Using a qualitative approach with a multidimensional analysis, this research explores how social, political, and religious dimensions were constructed to maintain regional stability and Javanese hegemony. The findings reveal that social relationships were built through